XPS study of the effects of long-term Ar+ ion and Ar cluster sputtering on the chemical degradation of hydrozincite and iron oxide. (October 2015) - Steinberger, R.; Walter, J.; Greunz, T.; Duchoslav, J.; Arndt, M.; Molodtsov, S.; Meyer, D.C.; Stifter, D.
Highlights: XPS study of different sputter techniques on possible Zn-based corrosions products. Systematic investigation using different sputter parameters for ion sputtering. Testing the capability of Ar cluster sputtering using different settings. In most cases a chemical alteration of the materials could not be hindered/avoided. Information of sputter profiles must not stand alone to deliver accurate results. Abstract: Monoatomic ion guns mounted on X-ray photoelectron spectrometers are frequently used for depth profiling to determine the depth distribution of various chemical compounds, or for surface cleaning. Sputtering with single ions may cause severe damage to some materials. Hence, in this study the influence of different sputter parameters on the degradation kinetics was examined. For comparison, the potential of Ar cluster sputtering was tested with the same materials, namely hydrozincite and FeO – two representatives of corrosion products that are susceptible to degradation. Chemical damage could only be minimized by cooling or cluster sputtering within a narrow cluster energy window.